Bayesian analysis of the suicidal idea in Peruvian adults - Jonatan Baños-Chaparro (Centro Provincial de Información de Ciencias Médicas, 2021)
Introduction: The suicidal idea is a wide term to describe a variety of views, desires and concerns about death. It is one of the main risk factors of suicidal death, although they refer differences as for sex. Objective: To analyze the differences according to sex regarding the suicidal ideation in Peruvian adults. Methods: A comparative, cross-sectional and non-experimental study was carried out, in April, 2021, of 366 Peruvian adults from the general population, selected by means of sampling by convenience with inclusion and exclusion criteria. To such an effect, the frequency inventory of suicidal ideation, and in the statistical analysis, the Mann-Whitney U-test of independent bayesian samples were used. Results: The average age was 29.64 and there a higher participation of the female sex (55.5 %). The bayesian analysis demonstrated that the observed data were more probable under the alternative hypothesis (BF10=53.477; δ=0.411; IC 95 %: 0.181-0.635), with a very strong evidence. This difference was higher in women (M=6.46) in comparison with men (M=5.83). Conclusions: The findings demonstrated that suicidal ideation is mainly presented in women, so that it is the most vulnerable group, reason why it needs a higher care of health professionals. In this respect, psychologists and psychiatrists play an important role to identify people at risk and provide the necessary help in advance for their intervention.